Stand -alone net zero energy container houses as temporary offsite working/living - Kim, J. R.; Bakhtiyarov, D.; Saliyev, D.; Zhumabekov, G.; Sailauova, N. (Nazarbayev University, 2014)
This paper is aimed to investigate and briefly analyze the conditions in Kazakhstan to predict the effectiveness of operation of standalone net zero energy container house. The description of Kazakhstani weather conditions as well as container house's characteristics is provided. The comparison was done between the specifications of solar, wind energy transformation technologies with the data collected in all regions of the country to check the feasibility of the project. Additionally, the brief description of stand-alone net zero energy container houses, including both interior-exterior design and energy control system, are provided.
Keywords: analyze; standalone; net zero energy; energy transformation; technologies; project